Systemic Immune Dysregulation in Early Breast Cancer Is Associated With Decreased Plasma Levels of Both Soluble Co-Inhibitory and Co-Stimulatory Immune Checkpoint Molecules - Rapoport, Bernardo L.; Steel, Helen C.; Hlatshwayo, Nomsa; Theron, Annette J.; Meyer, Pieter W. A.; Nayler, Simon; Benn, Carol-Ann; Smit, Teresa; Kwofie, Luyanda L. I.; Heyman, Liezl; Anderson, Ronald (Frontiers in Immunology, 2022)
Breast cancer cells exploit the up-regulation or down-regulation of immune checkpoint proteins to evade anti-tumor immune responses. To explore the possible involvement of this mechanism in promoting systemic immunosuppression, the pre-treatment levels of soluble co-inhibitory and co-stimulatory immune checkpoint molecules, as well as those of cytokines, chemokines, and growth factors were measured in 98 newly diagnosed breast cancer patients and compared with those of 45 healthy controls using multiplex bead array and ELISA technologies. Plasma concentrations of the co-stimulatory immune checkpoints, GITR, GITRL, CD27, CD28, CD40, CD80, CD86 and ICOS, as well as the co-inhibitory molecules, PD-L1, CTLA-4 and TIM-3, were all significantly lower in early breast cancer patients compared to healthy controls, as were those of HVEM and sTLR-2, whereas the plasma concentrations of CX3CL1 (fractalkine), CCL5 (RANTES) and those of the growth factors, M-CSF, FGF-21 and GDF-15 were significantly increased. However, when analyzed according to the patients’ breast cancer characteristics, these being triple negative breast cancer (TNBC) vs. non-TNBC, tumor size, stage, nodal status and age, no significant differences were detected between the plasma levels of the various immune checkpoint molecules, cytokines, chemokines and growth factors. Additionally, none of these biomarkers correlated with pathological complete response. This study has identified low plasma levels of soluble co-stimulatory and co-inhibitory immune checkpoint molecules in newly diagnosed, non-metastatic breast cancer patients compared to healthy controls, which is a novel finding seemingly consistent with a state of systemic immune dysregulation. Plausible mechanisms include an association with elevated levels of M-CSF and CCL5, implicating the involvement of immune suppressor cells of the M2-macrophage/monocyte phenotype as possible drivers of this state of systemic immune quiescence/dysregulation.